FORECAST ON THE MILITARY-POLITICAL SITUATION EMERGING IN THE WORLD AND THE CENTRAL ASIAN REGION - DUBOVTSEV, Georgy; GALYMZHANULY, Erlan (CENTRAL ASIA AND THE CAUCASUS, 2011)
Today, the effects of worldwide globalization are being felt far and wide, while the old international world order, which toppled in the first decade of the 21st century, has become one of its victims. Globalization has intruded into the spheres of the vitally important interests of individual states and the world community as a whole, which can be described as one of its worst impacts. This has added urgency to several extremely important problems, such as peace and universal security; arms control; disarmament; deterioration of the environment; demography; depletion of natural resources; energy production; space research; poverty and backwardness; drug trafficking and international terrorism. The negative charge of these transnational problems is immense; moreover, they are intertwined to form an entanglement of all sorts of inner ties and links. Globalization is gradually destroying all structures—national, political, economic, social, and others—the negative impact of which (ethnic separatism, confessional and ethnic clashes, consolidation of ethnic groups in the economy, corruption, social contradictions, etc.) require state interference. Today, however, the state is slowly but surely losing its functions, which is narrowing down its role. Today’s global players (countries, transnational corporations, and regional alliances) have mastered new methods and strategies: economic intrusion into domestic markets; fast movement of finances; migration of highly skilled human resources; the use of information as a weapon of struggle, etc. The wars have differed: new strategies rely on terrorist operations, the mass circulation of drugs, non-conventional types of weapons, etc. This has already changed the international security structure, thus creating new challenges and threats. Today, the West and the Islamic world are locked in a geopolitical confrontation which has assumed the form of a smoldering Middle Eastern conflict and the West’s determination to reduce its dependence on Middle Eastern oil. Most of the Muslim states are dead set against the West, its domination, and its desire to impose “alien” Western values on them. From time to time, the struggle assumes hypertrophied forms. The world is gradually acquiring several diversified models (the centers of military might will not necessarily be centers of economic power or cultural impacts); this means that in the future, the system of international relations will acquire several levels and several dimensions.